Outcomes of revisional bariatric surgery at a regional centre in United Kingdom - Ali, Muhammad; Odelberg, Wilhelm; Iqbal, Usama; Khan, Amir; Mirza, Salman (International Surgery Journal, 2022)
Background: Bariatric surgery has now been well established for long enough that revisional procedures have become more numerous and common, the importance to evaluate services and establish good evidence for our knowledge surrounding reoperations is vital. Methods: A retrospective analysis was conducted, for patients undergone revisional bariatric surgery between June 2010 and July 2017 at a single tertiary centre in the United Kingdom (UK). Revision rates and weight loss for the most common bariatric procedures were established, as well as the documented indications. Data was analysed with Mann-Whitney-U test. Results: The1619 bariatric procedures were recorded, of which 61 were revisional weight loss procedures. The most common performed primary procedure was gastric bypass (678). Revision rate for gastric band was highest (7%), followed by gastric bypass 5.6% and 2.60% for sleeve gastrectomy. The overall revision rate was 5%. Best weight loss outcomes were shown in conversion of gastric band to sleeve gastrectomy. Main indication for revision weight regain (30%) followed by gastric reflux (21%). Mean duration between primary and revisional procedure was 7 years. Conclusions: Most revisional surgery is performed within the first decade of primary procedure, with weight regain and GORD being most common causes. It is important that revisional surgery, its indications, prevalence, and risks are discussed with patients at the time of primary bariatric surgery.